EVALUATION OF RENT PAYMENTS IN STARA ZAGORA DISTRICT - P. Petkova; H. Momchilov (Trakia Journal of Sciences)
The Stara Zagora region is characterized by the fact that there is a large number of agricultural producers who do not have enough land of their own to optimize their production. This causes increased interest and competition between them for free agricultural land, fields and permanent grassland. The purpose is to trace the dynamics of rent payments in Stara Zagora district, through dynamic relative values. A comparative analysis of the relative values characterizing the dynamics was used.